2011
DOI: 10.1007/s10096-011-1496-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phenotypic methods and matrix-assisted laser desorption ionisation time-of-flight mass spectrometry for the identification of aero-tolerant Actinomyces spp. isolated from soft-tissue infections

Abstract: Aero-tolerant Actinomyces spp. are an under-recognised cause of cutaneous infections, in part because identification using conventional phenotypic methods is difficult and may be inaccurate. Matrix-assisted laser desorption ionisation time-of-flight mass spectrometry (MALDI-TOF MS) is a promising new technique for bacterial identification, but with limited data on the identification of aero-tolerant Actinomyces spp. This study evaluated the accuracy of a phenotypic biochemical kit, MALDI-TOF MS and genotypic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 9 publications
1
28
0
Order By: Relevance
“…Our results support previous findings that Actinomyces species can be reliably identified using MALDI-TOF MS (10)(11)(12), with all 12 of our tested isolates identified to the species level, as confirmed by molecular testing. Five isolates were correctly identified to the species level by MALDI-TOF MS despite identification scores only reaching genus-level confidence (ie, a p score of Ͻ2.0).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results support previous findings that Actinomyces species can be reliably identified using MALDI-TOF MS (10)(11)(12), with all 12 of our tested isolates identified to the species level, as confirmed by molecular testing. Five isolates were correctly identified to the species level by MALDI-TOF MS despite identification scores only reaching genus-level confidence (ie, a p score of Ͻ2.0).…”
Section: Discussionsupporting
confidence: 91%
“…Actinomyces species which are isolated from breast abscess samples may therefore be presumptively identified in the laboratory as diphtheroids based on their morphology and reported as diphtheroids of doubtful or uncertain significance. However, laboratories are increasingly adopting new methods of identification, such as MALDI-TOF MS (13), which allow rapid and increasingly reliable identification of this problematic group of organisms (10)(11)(12). Indeed, most of the cases in Lothian were identified after 2012, which is shortly after our laboratory started using MALDI-TOF MS. With 10 cases diagnosed in 2 years of using MALDI-TOF MS compared to 2 cases over 7 years without MALDI-TOF MS, it is clear that ease of identification is a major factor in the increased recognition of Actinomyces breast infections in our clinical setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification by MALDI-TOF MS has been analyzed for single genera of GPR, such as Corynebacterium (13)(14)(15), Actinomyces (16), Nocardia (17), Listeria (18), anaerobic GPR (19), and difficult-to-identify GPR (20,21). These studies were mostly done using the Bruker MALDI Biotyper system and indicated that sample preparation by the direct transfer procedure without additional modification is not sufficient for accurate identification of GPR but that a chemical extraction method is required.…”
mentioning
confidence: 99%
“…Several recent publications demonstrate the ability of MALDI-TOF MS to correctly and rapidly identify Actinomyces spp. (15,16,17,18). MALDI-TOF MS may be considered an alternative method for routine identification, provided the database is up to date.…”
mentioning
confidence: 99%